The Importance Of Previous Studies In Scientific Research (Journal of Namibian Studies : History Politics Culture, 2023)
Previous studies constitute foundational pillars throughout the investigative process, serving as vital guides and mentors in scientific research. From the initial spark of defining a research problem to the meticulous analysis and interpretation of results, prior scholarship illuminates each step. This article delves deeper into this paramount importance, exploring the multifaceted benefits of previous studies for both their formal structure and thematic content. It will empower researchers with the knowledge to present these vital resources rigorously and practically, thereby optimizing their potential utility in individual research endeavors.